2006
DOI: 10.1038/sj.embor.7400867
|View full text |Cite
|
Sign up to set email alerts
|

Snail genes at the crossroads of symmetric and asymmetric processes in the developing mesoderm

Abstract: Retinoic acid (RA) signalling ensures that vertebrate mesoderm segmentation is bilaterally synchronized, and corrects transient interferences from asymmetric left-right (L-R) signals involved in organ lateralization. Snail genes participate in both these processes and, although they are expressed symmetrically in the presomitic mesoderm (PSM), Snail1 transcripts are asymmetrically distributed in the L-R lateral mesoderm. We show that the alteration of the symmetric Snail expression in the PSM induces asynchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
1
31
0
Order By: Relevance
“…EMT-based escape involves 5 steps: (1) a post-mitotic cell breaking tight junction connections with its neighbors, (2) losing epithelial adherence (E-cadherin downregulation), (3) transiently acquiring motility and other mesenchymal characteristics, (4) epithelial exit, and (5) the re-formation of tight junctions between remaining cells across the space vacated (Morales et al, 2007). Despite the release of pro-endocrine cells from the trunk epithelium being proposed to involve EMT, concrete evidence of the actual process or components involved has yet to be provided.…”
Section: Delamination Of Pro-endocrine Cells and Isletogenesismentioning
confidence: 99%
“…EMT-based escape involves 5 steps: (1) a post-mitotic cell breaking tight junction connections with its neighbors, (2) losing epithelial adherence (E-cadherin downregulation), (3) transiently acquiring motility and other mesenchymal characteristics, (4) epithelial exit, and (5) the re-formation of tight junctions between remaining cells across the space vacated (Morales et al, 2007). Despite the release of pro-endocrine cells from the trunk epithelium being proposed to involve EMT, concrete evidence of the actual process or components involved has yet to be provided.…”
Section: Delamination Of Pro-endocrine Cells and Isletogenesismentioning
confidence: 99%
“…After being washed with PBS, embryos were transferred to an EC culture plate and incubated until HH stage 12/13 (omeprazole) or HH stage 15 (Z-VAD-FMK). Cells within the primitive streak were electroporated with Pitx2a-RCAS (45) or a chick Snail1-pcDNA3 construct (46). To visualize the electroporated cells, an eGFP reporter construct (pCAGGS-GFP) was used (47).…”
Section: Methodsmentioning
confidence: 99%
“…Whole mount in situ hybridization was performed as previously described (48). Antisense RNA probes for chicken Tbx18, Nodal, Wt1, Snai1, and Pitx2 were generated from full-length cDNA clones (8,23,46,49). Double color whole mount in situ hybridization was performed as previously described (50).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, in the chick it was shown that in the absence of RA signaling, snail1 expression is not affected in the LPM but starts to be asymmetrically expressed in the right anterior PSM. This asymmetric PSM expression of snail1 results in asymmetric expression of the cyclic genes snail2 and lfng and later leads to asynchronous somitogenesis [99]. In mouse, asymmetric somite formation seen in the absence of RA signaling [94] may be due to a misregulation of snail1 expression in the PSM, since it has been shown that in mice mutants for Rere there is an asymmetric snail1 expression in the PSM [95].…”
Section: Retinoic Acid Buffers the Psm From The Influence Of Lr Signalsmentioning
confidence: 99%
“…In both chick and mouse embryos, snail1 is transiently asymmetrically expressed in the right LPM and plays a role in organ lateralization [97,98]. Furthermore, it was shown that the period of asymmetric snail1 expression in the LPM coincides with the time window during which RA is necessary to protect the PSM from asymmetric signals [99]. Indeed, in the chick it was shown that in the absence of RA signaling, snail1 expression is not affected in the LPM but starts to be asymmetrically expressed in the right anterior PSM.…”
Section: Retinoic Acid Buffers the Psm From The Influence Of Lr Signalsmentioning
confidence: 99%